Implementasi Manajemen Berbasis Sekolah untuk Meningkatkan Mutu Pendidikan di SMP Negeri 17 Purworejo - Muhamad Churdaini (Cakrawala: Jurnal Kajian Manajemen Pendidikan Islam dan studi sosial, 2020)
This research is based on the importance of school-based management. In this regard, this study aims to determine the Implementation of School-Based Management to Improve the Quality of Education at SMP Negeri 17 Purworejo. This research is a qualitative research. Data collection used interviews, observation, and documentation, and the validity of the data used triangulation, and data analysis techniques included data collection, data reduction, data presentation, and drawing conclusions. This research resulted in four conclusions: (1) School autonomy in improving the quality of education at SMP N 17 Purworejo has been running according to the provisions of the applicable regulations. (2) School participation in improving the quality of education at SMP N 17 Purworejo is by involving all relevant school stakeholders. Participation is carried out in planning activities, policy making, as well as in the implementation of education in schools. (3) The leadership of the principal in improving the quality of education at SMP N 17 Purworejo is going well. The principal is able to carry out his role as a leader and manager in a balanced way. (4) School teamwork in improving the quality of education at SMP N 17 Purworejo is carried out with strong cohesiveness and togetherness, so that they are able to solve problems optimally.